Immune cell dynamics and the impact on the efficiency of transvascular antitumor interventional therapies in hepatocellular carcinoma patients - Sun, Yuan-Dong; Zhang, Hao; Li, Yuan-Min; Zhou, Chun-Xiao; Han, Jian-Jun (Frontiers in Immunology, 2024)
Objective This study investigates the impact of transvascular antitumor interventional therapies on immune cell dynamics and its correlation with disease control and progression-free survival (PFS) in hepatocellular carcinoma (HCC) patients. Methods A single-center observational case-control study was conducted with 119 HCC patients. Transvascular antitumor interventional therapy were administered based on patient-specific evaluations. Peripheral blood samples were collected before and within 28 days after the first treatment to analyze lymphocyte subsets and other immune cells. Results Higher counts of total white blood cells (WBCs), lymphocytes, monocytes, and basophils were significantly associated with disease control rate. Subgroup analysis revealed that abnormal BMI, diabetes, infection, and multiple lesions were significantly associated with T cell abnormalities. Age, abnormal BMI, hypertension, and abnormal AFP were linked to total T cell abnormalities. NK cells, B cells, Th cells, Tc/Ts cells, and CD4/CD8 ratios did not show significant differences in PFS probabilities. Conclusion Higher counts of WBCs, lymphocytes, monocytes, and basophils, play a crucial role in the effectiveness of HCC interventional therapy.